Quantification of lincomycin resistance genes associated with lincomycin residues in waters and soils adjacent to representative swine farms in China - Li, Liang; Sun, Jian; Liu, Baotao; Zhao, Donghao; Ma, Jun; Deng, Hui; Li, Xue; Hu, Fengyang; Liao, Xiaoping; Liu, Yahong (Frontiers in Microbiology, 2013)
Lincomycin is commonly used on swine farms for growth promotion as well as disease treatment and control. Consequently, lincomycin may accumulate in the environment adjacent to the swine farms in many ways, thereby influencing antibiotic resistance in the environment. Levels of lincomycin-resistance genes and lincomycin residues in water and soil samples collected from multiple sites near wastewater discharge areas were investigated in this study. Sixteen lincomycin-resistance and 16S rRNA genes were detected using real-time PCR. Three genes, lnu(F), erm(A) and erm(B), were detected in all water and soil samples except control samples. Lincomycin residues were determined by rapid resolution liquid chromatography-tandem mass spectrometry, with concentrations detected as high as 9.29 ng/mL in water and 0.97 ng/g in soil. A gradual reduction in the levels of lincomycin-resistance genes and lincomycin residues in the waters and soils were detected from multiple sites along the path of wastewater discharging to the surrounding environment from the swine farms. Significant correlations were found between levels of lincomycin-resistance genes in paired water and soil samples (r = 0.885, p = 0.019), and between lincomycin-resistance genes and lincomycin residues (r = 0.975, p < 0.01). This study emphasized the potential risk of dissemination of lincomycin-resistance genes such as lnu(F), erm(A) and erm(B), associated with lincomycin residues in surrounding environments adjacent to swine farms.